Efektivitas Game Edukasi Dalam Meningkatkan Pemahaman Konsep Matematika Dasar (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study aims to evaluate the effectiveness of educational games in enhancing the understanding of basic mathematics concepts through a Systematic Literature Review approach. The integration of educational games into the mathematics curriculum is expected to create an interactive and enjoyable learning experience for students. Literature searches were conducted across several academic databases, including Scopus, DOAJ, and Google Scholar, using keywords such as "educational games," "mathematics education," "game-based learning," and "basic mathematics understanding." Inclusion criteria encompassed articles published in English or Indonesian, discussing the effectiveness of educational games within the context of basic mathematics learning and employing valid research methodologies. Exclusion criteria included irrelevant articles, literature reviews without empirical data, and studies published before 2010. The data selection process was carried out in two stages: reviewing titles and abstracts to identify articles meeting the criteria, followed by a full reading of the articles to ensure relevance. Relevant data will be extracted to provide a comprehensive overview of the impact of educational games on basic mathematics understanding. This research is anticipated to offer further insights into the influence of demographic variables on the effectiveness of educational games and recommendations for developing a more inclusive and adaptive curriculum.Keywords: Educational games, understanding, mathematics concepts